Pengembangan Kompetensi Guru Berbasis Kebutuhan dalam Lembaga Pendidikan Islam - Nida Nur Aisyah; Awwal Muzakki Alkautsar (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze need-based teacher competence development as a strategic approach to improving learning quality and teacher professionalism in Islamic educational institutions. Using a qualitative method with a literature study approach, this research examines the process of teacher needs analysis, relevant competence development strategies, and their impact on institutional quality. The findings show that needs analysis—conducted through classroom observations, interviews, questionnaires, focus group discussions, and document analysis, serves as a critical foundation for identifying competency gaps. Development strategies such as need-based training, coaching–mentoring, professional learning communities, academic supervision, and the integration of educational technology are proven effective in enhancing teachers’ pedagogical, professional, and spiritual competencies. The impact of need-based development is evident in the improved quality of learning, the effectiveness of instructional methods, the integration of Islamic values, and the strengthening of a professional culture within the institution. Therefore, need-based competence development is a strategic approach to strengthening the overall quality and sustainability of Islamic educational institutions. Keywords: competence development, teacher needs analysis, teacher professionalism, learning quality, Islamic education.